Prevalence of metabolic syndrome in women with polycystic ovary syndrome attending a tertiary care hospital in West Delhi, India - Laul, Poonam; Miglani, Urvashi; Laul, Anish; Saxena, Pinkee; Malhotra, Megha; Kadam, V. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of the present study was to evaluate the prevalence of metabolic syndrome in women with polycystic ovary syndrome (PCOS). Methods: All the women attending the gynae out-patient department of our hospital were screened for polycystic ovary syndrome as diagnosed by the Rotterdam ESHRE/ASRM-sponsored PCOS consensus workshop group, 2004. Two hundred women with PCOS underwent screening for metabolic syndrome as defined by the national cholesterol education program adult treatment panel III (ATPIII) (2001) definition and the prevalence of metabolic syndrome was compared with two hundred age and BMI matched healthy control subjects. A multivariate logistic regression analysis was applied, and significant predictors identified for the prediction of metabolic syndrome. Results: The prevalence of metabolic syndrome among PCOS patients was 42 % in present study group as compared to 14 % in control group (p=0.01). The prevalence of metabolic syndrome was even higher in obese PCOS Vs non obese PCOS (52 % Vs 28.6 %). But even non-obese PCOS had higher prevalence of metabolic syndrome as compared to controls (28.6 % Vs 14 %). Conclusions: The study suggests a high prevalence of metabolic syndrome in patients with PCOS & thus it is important to screen all PCOS patients for manifestations of metabolic syndrome & its cardiovascular sequelae.